The Trouble with women evaluating the woman in the light of the broadcast journalism profession - Reyes, Katherine S.; University of the Philippines Diliman College of Mass Communication (Quezon City College of Mass Communication, University of the Philippines Diliman, 2000)
This research paper sought to find out if women possess the character traits that are incompatible with the standards of professional broadcast journalism. Qualitative document analysis was used in this study. Various books and articles on women and gender were reviewed and analyzed to prove or disprove the stereotypes of women. The results of this study reveal that: (1) Women are emotional; (2) Women gossip; and (3) Women exaggerate. The researcher concluded that women exhibit the traits which are uncalled for in the field of broadcast journalism. However, this should not discourage women from pursuing a career in broadcast journalism but rather this should serve as a caution for them to overcome these weaknesses.
Vita.
Thesis (A.B. Broadcast Communication)--University of the Philippines Diliman
Keywords: Women journalists -- Philippines